Anti VEFG Agents In Retinal Diseases - Khushboo Chawla (Delhi Journal of Ophthalmology)
Anti-vascular endothelial growth factor (Anti VEGF) agents are emerging as the most vital tool in the prevention of blindness due to ocular neovascularization in modern medicine. VEGFs are glycoproteins specific to endothelial cells, acting as key regulators of angiogenesis, vasculogenesis, and increasing vascular permeability. These are indicated in conditions such as diabetic macular edema (DME), vascular occlusions (RVO), Retinopathy of prematurity (ROP), neovascular age-related macular degeneration (nAMD), etc. The cost effect, need for frequent dosage, and side effects of increased IOP, infection, and cataract adds to the economic and disease burden. The newer research is now focused beyond anti-VEGF such as Angiopoietin and tyrosine kinase for vasculogenesis. This article reviews various anti-VEGF and angiogenic agents available in clinical practices.